2020
DOI: 10.21203/rs.3.rs-86997/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of the role of sex as a prognostic factor in critically ill adults with sepsis: a systematic review and meta-analysis

Abstract: Background: Incidence and sepsis-related mortality are failing, but sepsis continues to be a leading cause of admission and death in intensive care units (ICUs). Although the preceding evidence suggests sex-related risk differences for developing sepsis, the influence of sex on mortality outcomes remains unclear as previous studies showed discordant results. This systematic review assesed the independent effect of sex for mortality among critically ill patients with sepsis.Methods: Electronic databases were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
(129 reference statements)
0
1
0
Order By: Relevance
“…Three systematic reviews of sex differences in mortality of sepsis patients treated in the ICU have reported an absence of well-designed studies and significant heterogeneity [4][5][6]. In studies where sex differences in sepsis mortality are observed, differences between men and women's innate and adaptive immune response are cited [7], with greater protection in women attributed to the immune enhancing effects of estrogen, and male disadvantage related to the immunosuppressive properties of male androgens, particularly testosterone.…”
Section: Introductionmentioning
confidence: 99%
“…Three systematic reviews of sex differences in mortality of sepsis patients treated in the ICU have reported an absence of well-designed studies and significant heterogeneity [4][5][6]. In studies where sex differences in sepsis mortality are observed, differences between men and women's innate and adaptive immune response are cited [7], with greater protection in women attributed to the immune enhancing effects of estrogen, and male disadvantage related to the immunosuppressive properties of male androgens, particularly testosterone.…”
Section: Introductionmentioning
confidence: 99%